Chatter Vibration Comparison Between Normal Helix Angle and Variable Helix Angle in End Milling Process Based on Spectrum Analysis - Sonief, Achmad As'ad; Fauzan, Arda Nur; Azlan, Fachry; Bashori, Muhammad Aziz (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
Chatter vibration in machining processes is often found in cutting processes which will decrease the machining efficiency and the surface quality of the products. Chatter is a relative vibration of the cutting tool and workpiece caused by the fluctuation of cutting force that is concerned to be a self-excited vibration. The variable Helix Angle Cutting tool which has pitch angle variation will also inflict different tooth passing frequencies on the flute that stand contiguous and trim the resonance frequency. This research aims to compare chatter vibrations that occurred between Normal Helix Angle and Variable Helix Angle cutting tool based on spectrum analysis on cutting parameter variety (depth of cut; rotation speed; feed rate milling). The outcome is spectrum analysis can detect the chatter phenomenon, measure the natural frequency (38-42 Hz), and also compare chatter vibrations between two tools appropriately.